The Effect of Value Clarification Technique Learning Models and Learning Styles on the Achievement Learning Outcomes of Class VIII MTs Al-Hasanah Tanjung Leidong, Labura District - Siti Halimah; Zulfahmi Lubis; Saidatun Nisa Nasution (BIRCU, 2020)
The purpose of this study was to determine: (1) the influence of the value clarification technique (VCT) learning model on student learning result. (2) Knowing the influence of learning styles on student learning result. (3) Knowing the interaction between learning models and learning styles on student learning result. The population of this study were students of class VIII MTs Al-Hasanah Tanjung Leidong Labuhan Batu Utara consisting of three classes. The sample chosen for the class with the VCT learning model was class VIII-3 with 30 students, while students who were taught using the expository model were 32 students. The cluster random sampling technique is influenced by analysis of variance at a significant level (α = 0.05) followed by Scheffe. The results of this study are: (1) the average value of students taught with the VCT learning model (= 33.6) is higher than students taught with the expository learning model (= 24.68) with Fcount 0.0023 < Ftable 3,988. (2) The average value of learning outcomes Akidah Akhlak with visual learning styles (= 27.5), auditory (= 29.56) and kinesthetic (= 28.26) with Fcount = 0.068 < Ftable = 3,988. (3) There is an interaction between learning models and learning styles on students' learning outcomes Akidah Akhlak with Fcount 28.96 < Ftable 3,988. Based on the data analysis, it can be concluded that students with visual and auditory characteristics, the appropriate learning model is the VCT, while students with the kinesthetic learning style are expository. The implication is that teachers must be trained in how to understand student learning styles. Thus it is suggested that in planning the learning process the characteristics of students must be considered.